The adventures of a South Pole pig : a novel of snow and courage - Kurtz, Christopher (Harcourt Children's Books, Houghton Mifflin Harcourt, 2012)
"Flora the pig ditches the sedentary life on the farm for an adventure in Antarctica, where she escapes the knife and lives her dream of pulling a sled with a team of dogs"--